Helicanus as 'a figure of truth, faith and loyalty' in Shakespeare's Pericles - Ali Termizi, Arbaayah; Toh, Florence Haw Ching (Center for Promoting Ideas, 2012)
Pericles has been the focus of most Shakespearean scholars, discussing issues ranging from the play’s narrative sources to the protagonist’s leadership qualities. But the present paper will center its arguments on Helicanus, the neglected servant character of the play. Although loyalty is assumed in master-servant relationships during the Renaissance, the paper provides evidence that corrupted practices within the Elizabethan ruling class and its subordinates overcomes the need to be loyal. Despite being surrounded by the prevailing temptation for power, Helicanus remained as an epitome of loyalty in his service towards his master, Pericles. The paper extracts examples from relevant scenes in the play depicting portrayals of loyalty displayed by this servant character towards Pericles. In short Helicanus’ loyalty becomes the fundamental drive which elevates Pericles’ status in the play. Therefore, the study aims to heighten the appreciation of Shakespeare’s Pericles through the understanding and emphasis of the significance of its dramatic servant characters.